STRATEGI GURU DALAM MENGATASI KESULITAN SISWA MEMBACA AL-QUR’AN DI MIN 22 HULU SUNGAI TENGAH - Ubaidillah Ubaidillah (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
The teacher’s strategy in overcoming students’ difficulties in reading the Qur’an properly is highly expected, because with good/accurate strategies it will make learning interesting and fun, so that existing goals can be achieved. Based on this statement, the focus of this research is the teacher’s strategy in overcoming students’ difficulties in reading the Qur’an at MIN 22 Hulu Sungai Tengah and the supporting and inhibiting factors. The purpose of this study was to find out the teacher’s strategy in overcoming students’ difficulties in reading the Qur’an at MIN 22 Hulu Sungai Tengah and the supporting and inhibiting factors. The type of research used is field research and uses a qualitative descriptive approach. The data source for this research was one of the teachers of the Qur’an Hadith subject, 6 students, the head of the madrasa, administrative staff, and data relating to the issues discussed. Data collection techniques are carried out by means of observation, interviews, and documentation. The data processing uses data reduction, data display, and data verification. Then analyzed using descriptive qualitative method. The results showed that: 1) the learning strategy used by the Qur’an Hadith teacher in overcoming students' difficulties in reading the Qur’an was an expository learning strategy, namely a strategy in which the procedure and implementation of learning activities were centered on the teacher, then a question and answer learning strategy namely the teacher can stimulate students’ way of thinking and guide them in understanding learning material, and group learning strategies, namely students are active in learning activities. 2) Supporting factors, there is an interest in learning to read the Koran and the desire to read and learn from the students themselves, as well as facilities and infrastructure that facilitate the implementation of learning. The inhibiting factor is the low interest in learning to read students which greatly influences the achievement results in a lesson and students' reading ability is classified as low, because not all students have the same level of intelligence.